EFFICIENCY OPTIMIZATION OF A STEAM POWER PLANT OUTPUT 800 kW USING SHELL AND FIBER FUEL AT PALM OIL MILL PTPN IV AIR BATU - Rufinus Nainggolan; Marlon Sibarani; Suadi; Positron Bangun; Baringin Sibarani; Joko Sutrisno (Yayasan Sinergi Multidimensi Kreatif, 2025)
At Palm oil mill PTPN IV Air Batu, steam boiler and steam turbine is a combination of steam power plant equipment to produce steam and electrical energy. This steam boiler is a type of water tube boiler TAKUMA N-600SA brand with specifications working pressure 22 Bar, Temperature 340OC. The steam produced by the boiler is used to drive a Dresser Rand Type 550W steam turbine for generating 800 kW of electrical power and for steam needs for the boiling process, sterilization of palm oil. In this study the author conducted an analysis of the performance of the boiler and steam turbine, also analyzed the fuel used as a source of heat energy for boiler operations, each are palm shells and fibers. Analysis of the fuel needs of a mixture of shells and fibers at Palm oil mill PTPN IV Air Batu, then for the composition of the three biomass components are shells and fibers with varying ratios: 75%: 25%; 50%: 50%, and 25%: 75%, then the calorific value of each is LHV = 14374.5 kJ / kg, LHV = 12411 kJ / kg, and LHV = 10447.5 kJ / kg. The results of the calculation of the respective fuel needs: 1.617 Ton / Hour, 1.872 Ton / hour, and 2.225 Ton / Hour. From the steam turbine specification data with an output power of 800 kW, the turbine inlet steam pressure is 20 Bar, temperature 340 OC, and steam capacity of 6 Ton/Hour and turbine outlet steam pressure of 3.5 Bar, then through performance analysis, the isentropic efficiency is obtained at 92.32%, and the overall efficiency of the steam power plant is 12.40%.